Science Teachers’ Knowledge, Beliefs, and Practices towards learning Science during Covid-19 Pandemic Outbreak - Upadhyaya, Indra Raj; Ghimire, Paras Mani (Interdisciplinary Research in Education, 2022)
The virtual mode of classes was accepted as the universal method across the globe during the pandemic. However, researchers found different challenges, barriers, and obstacles in virtual mode. It is crucial to understand how classroom practices are going during the pandemic, particularly for science, which is a practical and activity-based subject. Thus, this study aimed to discover what knowledge, beliefs, and practices science teachers had regarding science learning during the pandemic. In the study, 83 science teachers, were surveyed using a Google form with 12 items. The questionnaires covered curricular goals, teacher training, student regulations, modes of instruction, best strategies and approaches to teaching, the effectiveness of virtual classes, their obstacles, the evaluation of students, and suggestions for implementing virtual classes effectively. According to the results obtained, conclusions were drawn, and the study's implications were discussed.